Equilibrium-Informed Trading with Relative Performance Measurement - Qiu, Zhigang (Journal of Financial and Quantitative Analysis, 2017)
This article analyzes the informative trading of professional money managers within a rational-expectations equilibrium model in which managers care about their performance relative to their peer group. I find that the existence of uninformed managers causes informed managers with relative performance concerns to trade less informatively, engendering less informative prices. When managers are differentially informed, they need to forecast the average performance based on private signals, and each manager may place more weight on the private signal if the signal provides good information about the average performance. The price aggregates those signals and thus becomes more informative.